Entrepreneurial intentions of the students of the college for teacher education - Milošević, Bojan; Janković, Milenko; Damnjanović, Jelena (Sociološki pregled, 2023)
Of greawt importance are the readiness and capacity of future educators to recognize different specific needs of children and families in the local community and to analyze what the local community offers and what else may be offered. The research is aimed at testing the planned behaviour of students/future educators, having in mind their perception of potential entrepreneurial activity after completing their studies. The research involved 117 students who filled in the questionnaire for surveying their entrepreneurial intentions. It has been established that the subjective norm is not important in the intention of opening one’s own enterprise. The obtained results are similar to those in other countries, and that is why the experience of their educational systems can be appreciated regarding the implementation of educational subjects and courses in the educational system programs of the Republic of Serbia.